Proteomic Analysis of Porcine Pre-ovulatory Follicle Differentiation Into Corpus Luteum - Likszo, Pawel; Skarzynski, Dariusz J.; Moza Jalali, Beenu (Frontiers in Endocrinology, 2019)
Luteinization of the follicular cells, following LH surge, causes extensive molecular and structural changes in preovulatory follicles (POF) that lead to ovulation and ultimate formation of the corpus luteum (CL). The objective of this study was to identify proteins expressed in porcine POF before the LH surge and newly formed CL, 2-3 days after ovulation and evaluate proteome changes associated with formation of CL from a follicle. We used 2D-gel electrophoresis based proteomics and tandem mass spectrometry followed by functional analysis using Ingenuity Pathway analysis (IPA) to evaluate functional pathways associated with luteinization process. Protein lysates were prepared from isolated POFs and from newly formed CL. A total of 422 protein spots were identified in both the structures. 15 and 48 proteins or their proteoforms were detected only in the POFs and CL, respectively. IPA analysis of POF proteome showed that most of the follicular proteins were involved in cellular infiltration, endoplasmic stress response and protein ubiquitination pathway. Most of the early luteal proteins were associated with steroid metabolism, cell death and survival, free radical scavenging and protein ubiquitination pathway. A comparison of follicular proteome with that of early luteal proteome revealed that 167 identified proteins or their proteoforms were differentially regulated between POFs and newly formed CL (p < 0.05 and a fold change of > 1.8). Proteins that were significantly more abundant in follicles included cAMP dependent protein kinase, histone binding protein RBBP4, reticulocalbin, vimentin and calumenin; more abundant luteal proteins included albumin, farnesyl diphosphate synthase, serine protease inhibitors, elongation factor-1, glutaredoxin and selenium binding protein. Proteins that were significantly altered with luteal formation were found to be associated with cholesterol biosynthesis, cell death and survival, and acute phase response. Moreover, upstream regulators of differentially abundant protein in CL were identified that included insulin growth factor-1, sterol regulatory element binding transcription factor-1 and nuclear factor erythroid-derived 2. We have identified novel proteins that advance our understanding of 1) processes associated with differentiation of POFs into CL 2) possible mechanisms of luteal cell survival and 3) pathways regulating steroidogenesis in newly formed CL.